Combination of bisacodyl suppository and 1 L polyethylene glycol plus ascorbic acid is a non‐inferior and comfortable regimen compared to 2 L polyethylene glycol plus ascorbic acid. Issue 4 (11th November 2019) - Kim, Sun Hwa; Kim, Eun Ran; Kim, Kyunga; Kim, Tae Jun; Hong, Sung Noh; Chang, Dong Kyung; Kim, Young‐Ho
Abstract : Background and Aim: Appropriate bowel cleansing before colonoscopy is an important factor in increasing the detection rate of lesions. Low‐volume polyethylene glycol (PEG) plus ascorbic acid (PEG‐Asc) reduces the dosage of bowel preparation agent, but still presents discomfort to patients. The primary aim of the present study was to compare the efficacy of bowel cleansing between 2 L PEG‐Asc (control) and 1 L PEG‐Asc with bisacodyl suppository (suppository) groups, and the secondary aim was to investigate complications and tolerability between the two groups. Methods: This was a single‐center prospective randomized controlled study. We identified 168 patients scheduled for colonoscopy between August 2017 and January 2018 and randomly assigned them to the control or to the suppository groups. Efficacy of bowel cleansing was assessed using the Boston Bowel Preparation Scale (BBPS), and side‐effects were surveyed using questionnaires. Results: No significant difference was detected in baseline characteristics including insertion and withdrawal times, and adenoma detection rates between the two groups. Total BBPS score was 7.93 ± 1.06 and 7.74 ± 1.02 in the control and suppository groups, respectively ( P  = 0.22). Incidence of abdominal pain and nausea was not statistically different, whereas that of sleep disturbance and anal discomfort was higher in the control group. ( P  = 0.00). Conclusions: One liter PEG‐Asc with bisacodyl suppository resulted in an equivalent bowel‐cleansing outcome with reduced patient discomfort compared to 2 L PEG‐Asc. Therefore, PEG‐Asc with bisacodyl suppository represents a potential alternative and increases patient compliance with bowel preparation.